Bonding strength characteristic of self compacting concrete incorporating fly ash - Kurniawan, Agus; Shafiq, Nasir; Nuruddin, M Fadhil (2008)

(untitled)
The choice of Self Compacting Concrete (SCC) is because of high workability of this new material. SCC has been developed for several years to achieve more capability and more performance in term of strength, rheology and durability. In spite of compressive strength and other properties, bonding strength characteristic of SCC is much less understood, especially SCC incorporating fly ash. Malaysia country produces plenty of fly ash as waste material which can influence to the natural conservation. Using fly ash as waste materials as replacement of cement in SCC can reduce significantly of fly ash, so using fly ash is big concern of environmental safety and nature conservation. Pull out test was done to know the capability of bonding strength of this material. The water binder ratio appears to govern the bonding strength capacity.